Acceptance and Use of Digital Technology by Students in India After the Covid-19 Pandemic - Singh, Chandra B P (Universitas Pendidikan Ganesha, 2024)
After COVID 19 it was pertinent to ascertain acceptability and usage of digital technology by learners in India. Not all learners had similar behavioural intention of using digital technology. Taking it into consideration the study aimed to analyze learning styles of learners and trace its functional linkages to continuance usage of digital technology. Learners (n 242) who had skills of using mobile internet technology participated in the study. It was an empirical study based on qualtrics survey design. An attempt was made to substantiate model of structural linkages of constructs by Smart PLS-SEM technique. The study noted a set of findings: learners irrespective of their learning styles showed a willingness to continue usage of digital technology for open learning resources; paced learners had a direct linkage to use behaviour meaning that they were more organized and faster while using of digital tools for optimization of results; and hybrid-motivated learners had a strong behavioural intention for e-learning. Digital infrastructure in schools, if mismatched learning styles might result in a problem of use behaviour. Learners could be encouraged to participate in digital learning programme for maximization of gains. High acceptance and less use of digital technology required to be attended to address the gap between behavioural intention and use behaviour. The findings focused on learning styles that would help bridge a gap between acceptance and use of digital technology for school learning programme.